Managing Innovation in Kazakh small and medium-sized enterprises - Scharff, W.; Kurmanov, N.A.; Baigabulova, K.K.; Aibossynova, D.A. (Вестник Карагандинского университета, 2016)
The formation of an innovative economy in Kazakhstan is a complexity of economic, social, and political issues. An effective use of research findings and developments in the real economy is most important in terms of Kazakhstan’s successful competitiveness, assurance for high economic growth, improved quality of life, and to help realize other innovative priorities. In these circumstances, innovation management and development is becoming more relevant as the basis for developing Kazakh companies, by way of a defined set of relevant technical, operational, organizational, marketing, and financial operations. The purpose of this study is to identify characteristics and practical recommendations for the development and further improvement of management mechanisms relating to the innovative activity of enterprises in Kazakhstan.
Keywords: innovation; innovation process; enterprise innovative activity; commercialization of technologies; demand for innovation